2022
DOI: 10.1002/mame.202200270
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Nanofibers of SMEC Sheets: A New Approach to Control Self‐Folded Shape by Uniaxial Stretching

Abstract: Shape‐memory elastomer composite (SMEC) sheets, made of a honeycomb structured electrospun poly(ε‐caprolactone) (PCL) fiber mat embedded in a silicone (PDMS) elastomer, fold on themselves upon uniaxial traction. The self‐folding of the composite sheet originates from a bi‐layered structure obtained by a simple one‐step impregnation process. Indeed, the impregnation of a structured PCL fiber mat by oily PDMS in a flat Teflon mold leads, after curing, to an asymmetric composite sheet made of one PDMS flat thin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[23,24] Despite the qualitative similarity between Figure 1f-h and these older examples, the behavior of stretch-release-induced bending of elastic-plastic composites may be more complex. [2,5,10,12] First, the response of commercial polymer films such as in Figure 1 is often anisotropic such that long strips cut along two orthogonal directions may show distinct bending behaviors suggesting some anisotropy in the polymer due to the manufacturing process. Second, if stretched to a large extent, the sign and direction of the curvature may both flip, [5] an observation that is altogether nonintuitive.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…[23,24] Despite the qualitative similarity between Figure 1f-h and these older examples, the behavior of stretch-release-induced bending of elastic-plastic composites may be more complex. [2,5,10,12] First, the response of commercial polymer films such as in Figure 1 is often anisotropic such that long strips cut along two orthogonal directions may show distinct bending behaviors suggesting some anisotropy in the polymer due to the manufacturing process. Second, if stretched to a large extent, the sign and direction of the curvature may both flip, [5] an observation that is altogether nonintuitive.…”
Section: Research Articlementioning
confidence: 99%
“…Beyond our fundamental interest in plasticity effects in layered systems, [ 5–8 ] we are motivated by the potential for origami engineering where shape morphing can be induced in metal–plastic laminates by a simple loading–unloading protocol. Indeed such a stretch–release approach to origami has been explored previously, [ 1,3,4,9–11 ] and Nelson et al [ 3,4 ] have coined the evocative term mechano‐activated shape morphing, a term that we have adopted in the title of this article. Tang et al [ 9 ] showed especially beautiful examples of complex shapes realized by this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation